2022
DOI: 10.1177/09544119211072971
|View full text |Cite
|
Sign up to set email alerts
|

Validation of wearable inertial sensor-based gait analysis system for measurement of spatiotemporal parameters and lower extremity joint kinematics in sagittal plane

Abstract: Wearable inertial sensor-based motion analysis systems are promising alternatives to standard camera-based motion capture systems for the measurement of gait parameters and joint kinematics. These wearable sensors, unlike camera-based gold standard systems, find usefulness in outdoor natural environment along with confined indoor laboratory-based environment due to miniature size and wireless data transmission. This study reports validation of our developed (i-Sens) wearable motion analysis system against stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 49 publications
0
1
1
1
Order By: Relevance
“…In contrast to previous studies on slower activities (e.g., walking), our study showed lower correlations and larger RMSEs between the lower limb joint angle waveforms measured by the IMUs system and the optical motion capture system during running ( Al-Amri et al, 2018 ; Patel et al, 2022 ). Similar results were obtained in some dynamic tasks (e.g., jumping and soccer athletic manoeuvres), which may indicate that more caution should be taken when applying the IMUs system to more dynamic sports ( Akins et al, 2015 ; Al-Amri et al, 2018 ).…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to previous studies on slower activities (e.g., walking), our study showed lower correlations and larger RMSEs between the lower limb joint angle waveforms measured by the IMUs system and the optical motion capture system during running ( Al-Amri et al, 2018 ; Patel et al, 2022 ). Similar results were obtained in some dynamic tasks (e.g., jumping and soccer athletic manoeuvres), which may indicate that more caution should be taken when applying the IMUs system to more dynamic sports ( Akins et al, 2015 ; Al-Amri et al, 2018 ).…”
Section: Discussioncontrasting
confidence: 99%
“…As sensor technology has advanced, wearable and soft sensors can now be used to perform cost-effective and easy analyses [24]. Spatial-temporal and kinematic variables can be further calculated in gait analysis [29], [30]. The inertial sensors comprise a gyroscope, an accelerometer, and a magnetometer, which enable economical measurements of gravitational force and acceleration.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Los trastornos del movimiento se pueden originar por condiciones genéticas, derrames cerebrales, lesiones traumáticas, enfermedades del sistema nervioso, infecciones, por efectos secundarios de medicamentos y otros factores. Un historial de presión arterial alta, enfermedades como diabetes, la edad avanzada, y en algunos casos la adopción de malas posturas, incrementan el riesgo de trastornos del movimiento (Patel et al, 2022).…”
Section: Introductionunclassified